2017
DOI: 10.1371/journal.pone.0176838
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus ficuum phytase activity is inhibited by cereal grain components

Abstract: In the current study, we report for the first time that grain components of barley, rice, wheat and maize can inhibit the activity of Aspergillus ficuum phytase. The phytase inhibition is dose dependent and varies significantly between cereal species, between cultivars of barley and cultivars of wheat and between Fusarium graminearum infected and non-infected wheat grains. The highest endpoint level of phytase activity inhibition was 90%, observed with grain protein extracts (GPE) from F. graminearum infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
(30 reference statements)
4
16
0
Order By: Relevance
“…It has been previously demonstrated that the phosphatase activity of soil-derived enzymes might be inhibited in the presence of aluminum hydroxides [40]. Moreover, Cu 2+ and Fe 2+ have been reported as strong inhibitors of several phosphatases and phytases from different organisms, such as S. ruminantium or Klebsiella terrigena [41,42]. These proteins were also strongly inhibited in the presence of Zn 2+ , which only has a minor effect on the activity of Pho16B.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously demonstrated that the phosphatase activity of soil-derived enzymes might be inhibited in the presence of aluminum hydroxides [40]. Moreover, Cu 2+ and Fe 2+ have been reported as strong inhibitors of several phosphatases and phytases from different organisms, such as S. ruminantium or Klebsiella terrigena [41,42]. These proteins were also strongly inhibited in the presence of Zn 2+ , which only has a minor effect on the activity of Pho16B.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that barley crude protein extracts inactivate microbial phytases via aspartic acid proteinase activity, rather than through classical enzyme inhibition [35]. Activity inhibition-based purification and MS analysis of inhibitory fractions identified HvNEP-1 as a potent inhibitor of fungal phytases [36].…”
Section: Introductionmentioning
confidence: 99%
“…There are no known reversible proteinaceous inhibitors of phytases. Instead, plants appear to rely on proteases, e.g., to counter pathogen-secreted phytases [ 92 ]. This suggests that the activity of PAPhy_a is tightly controlled by the chemical environment, likely the pH, and/or localization.…”
Section: Phytasesmentioning
confidence: 99%